Prevalence and associated factors of BRCA1/BRCA2 mutations according to genetic testing indications in breast cancer patients at Maha Vajiralongkorn Thanyaburi Hospital - Khueachanta, Suriya; Siripin, Watcharee (Journal of Medical and Public Health Region 4, 2026)
Hereditary breast and ovarian cancer caused by BRCA1/BRCA2 gene mutations is a significant health problem, with mutation carriers having significantly higher risk of developing breast and ovarian cancer compared to the general population. This study aimed to investigate the prevalence of BRCA1/BRCA2 gene mutations and their association with genetic testing indications in breast cancer patients. A descriptive study was conducted among 174 female breast cancer patients receiving treatment at Maha Vajiralongkorn Thanyaburi Hospital from October 20, 2022 to December 31, 2024. Data were analyzed using Chi-square test. The study found 19 cases with BRCA1/BRCA2 gene mutations, representing a prevalence rate of 10.9%, comprising 13 BRCA1 mutations (7.5%) and 6 BRCA2 mutations (3.4%). Genetic testing indications significantly associated with mutations included having multiple primary breast cancers in patients aged 46 - 50 years (p = 0.027), specific family history in patients aged 50 years or older (p = 0.043), and triple-negative breast cancer (TNBC) (p = 0.006). TNBC patients had a mutation rate of 17.4% compared to 4.5% in non-TNBC patients, and patients with negative estrogen receptor had a mutation rate of 14.7% compared to 3.2% in patients with positive estrogen receptor (p = 0.018). This study demonstrates a BRCA gene mutation prevalence consistent with other studies and genetic testing indications can effectively screen high-risk patients.